2004
DOI: 10.1007/s00330-004-2618-4
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative disorders of the spine

Abstract: Patients with back pain and degenerative disorders of the spine have a significant impact on health care costs. Some authors estimate that up to 80% of all adults experience back pain at some point in their lives. Disk herniation represents one of the most frequent causes. Nevertheless, other degenerative diseases have to be considered. In this paper, pathology and imaging of degenerative spine diseases will be discussed, starting from pathophysiology of normal age-related changes of the intervertebral disk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…It has been suggested that in case of an abnormal facet positioning, the distribution of mechanical loads and stress in that spinal segment changes in a way that the risk of degeneration and instability increases [12,17,25,33]. However, this possibility and even the status of the facet joints as to their orientations have not been examined in degenerative scoliosis with or without a rotational component.…”
Section: Introductionmentioning
confidence: 95%
“…It has been suggested that in case of an abnormal facet positioning, the distribution of mechanical loads and stress in that spinal segment changes in a way that the risk of degeneration and instability increases [12,17,25,33]. However, this possibility and even the status of the facet joints as to their orientations have not been examined in degenerative scoliosis with or without a rotational component.…”
Section: Introductionmentioning
confidence: 95%
“…Degenerative change of the spine is a common age-related vertebral alteration (Gallucci et al, 2005;Roh et al, 2005;Freund and Sartor, 2006;Pytel et al, 2006;Kalichman and Hunter, 2007;Ruan et al, 2007;Shedid and Benzel, 2007). The vertebral bodies are interconnected by the intervertebral discs (fibrocartilage), which are called symphyses.…”
Section: Introductionmentioning
confidence: 99%
“…Such a mechanical loading imbalance could accelerate the local degradation of the tissue and trigger degenerative processes. Any asymmetrical loading of the facet joints contributes to the development of facet osteophytes, cartilage erosion, fibrillation, or denudation, as well as narrowing of the joint space and neural foramen, and formation of synovial cysts [286]. In addition, facet orientation and tropism, an asymmetrical orientation of the bilateral facets, also appear to be predisposing factors for the development of degenerative spondylolisthesis [287] and facet joint degeneration [288], especially in the lumbar spine.…”
Section: Artificial Disc Implantsmentioning
confidence: 99%
“…Spinal asymmetry might be associated with a greater risk of spinal degeneration [192,283,[285][286][287][288][289][290][291][292]. Osteophytes decrease lumbar segmental motion [294].…”
Section: Facet Joint Degenerationmentioning
confidence: 99%